Ocorrência da brucelose bovina em alguns municípios da bacia leiteira de Belém, estado do Pará - Eliana Maria Lobato Moraes (1990)
The occurence of bovine brucellosis was studied in 92 farms from four countries from the milk region of Belém, state of Pará. The tests used were, the milk ring test (MRT), in which 32,60% out the farms studied were reagents, the why plate agglutination test (WPT), which detected 4,43% of reactors mammary glands, and the rapid plate agglutination test (RPA), in which it was detected 9,28% positive and 14.03% suspected bovine reactors for brucellosis. In a comparison between WPT and RPA tests it was found a heterogeneity in variance among positive, suspect and negative results. Using biochemical tests it was identified 3,10% positive cultures of Brucella abortus out of 129 milk sample studied, althrough no cinfirmation by biotype screeming had been performed.